2002
DOI: 10.1074/jbc.m111391200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Salivary Immunosuppressive Protein from Ixodes ricinus Ticks

Abstract: In tick salivary glands, several genes are induced during the feeding process, leading to the expression of new proteins. These proteins are typically secreted in tick saliva and are potentially involved in the modulation of the host immune and hemostatic responses. In a previous study, the construction and the analysis of a subtractive library led to the identification of Ixodes ricinus immunosuppressor (Iris), a novel protein, differentially expressed in I. ricinus salivary glands during the blood meal. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
144
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 22 publications
4
144
0
2
Order By: Relevance
“…Molecular Modeling-Iris had previously been found to be similar to the pig leukocyte elastase inhibitor (35). In addition, membership in the serpin superfamily was confirmed by the high conservation of consensus residues identified by Irving and colleagues (45).…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Molecular Modeling-Iris had previously been found to be similar to the pig leukocyte elastase inhibitor (35). In addition, membership in the serpin superfamily was confirmed by the high conservation of consensus residues identified by Irving and colleagues (45).…”
Section: Resultsmentioning
confidence: 76%
“…Plasmid Construction, Protein Expression, and PurificationThe coding sequence for Iris (formerly Seq24; accession number AJ269658) was subcloned from vector pCDNA3.1-V5-His/Iris (35) between the KpnI/AgeI restriction sites of vector pBlueBac4.5-V5-His (Invitrogen) in-frame with the coding sequence of the V5 and His epitopes at the C terminus. Recombinant baculoviruses were made by recombination between pBlueBac/Iris and Bac-N-Blue linear DNA virus (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with vertebrate Oatp/OATP genes that show multiple tissue expression patterns (St-Pierre et al, 2002;Gao et al, 2005;Choudhuri et al, 2003), our RT-PCR expression analyses data revealed that AamOatp mRNA is both constitutively and ubiquitously expressed, as it was it is expressed in all tested organs of ticks that fed for 1-7 days. Transcriptional regulation of tick genes has been shown in response to blood meal feeding, being either shut down or induced, up-or down regulated (Leboule et al, 2002a;Leboule et al, 2002b;Mulenga et al, 2001;Rudenko et al, 2005). In the case of AamOatp, the switch in expression pattern, from being predominant in the midgut during the first 5 days of feeding and the ovary, by day 7 of feeding suggest that AamOatp is transcriptionally regulated in response to changing physiological needs as tick feeding progresses.…”
Section: Discussionmentioning
confidence: 99%